Pembuatan Hair Extension dari Bahan Tanaman Serat Lidah Mertua (Sansevieria Trifasciata) - Ratna Zulfa Aprilia; Kuswidyaningrum N J (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Lidah mertua is an ornamental plant that has a variety of colors, shapes and sizes. The Lidah mertua plant produces fine fibers on its leaves. The author uses Lidah mertua fiber to make hair extensions. The aim of this research is to determine the process of making hair extensions from plant material from Lidah mertua fiber (Sansevieria Trifasciata), the suitability of the product, and the level of public preference for hair extension products from Lidah mertua fiber (Sansevieria Trifasciata). Data collection uses Observation, Documentation, Experimentation, Literature, Questionnaire and Interview methods. Data Analysis in the form of Quantitative and Public Testing. Making hair extensions from Lidah mertua (Sansevieria Trifasciata) fibers begins with selecting Lidah mertua, shaving to produce fiber, washing and drying, coloring stage, and applying hair serum. The results of the feasibility test from 3 validators were declared feasible in experiment I, namely hair extensions from Lidah mertua (Sansevieria Trifasciata) fibers using clothing dye. he liking level of 60 respondents was stated to be appropriate and liked by the public. Hair extension products using Lidah mertua (Sansevieria Trifasciata) fibers require further trials so that they can be used in the long term and create more varied hair extension colors.